2009
DOI: 10.4049/jimmunol.0900196
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Ablation Enhances Hematopoietic Recovery following Cytotoxic Antineoplastic Therapy in Aged Mice

Abstract: Cytotoxic antineoplastic therapy is widely used in the clinic as a treatment for malignant diseases. The treatment itself, however, leads to long-term depletion of the adaptive immune system, which is more pronounced in older patients, predominantly due to thymic atrophy. We and others have previously shown that withdrawal of sex steroids is able to regenerate the aged thymus and enhance recovery from autologous and allogeneic hematopoietic stem cell transplant. In this study we have examined the effects of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 82 publications
1
36
0
1
Order By: Relevance
“…It has been suggested that the thymic stroma is the initial target of androgen-induced thymic atrophy [57,67] ; however, these studies failed to account for the role of bone marrow and thymic lymphoid progenitors, which are also significantly increased following castration [13,16,17] . In the bone marrow, there is improved function in most steps of haematopoiesis from the earliest long-term haematopoietic stem cell (HSC) through to thymic progenitors [pers.…”
Section: Castration and Ovariectomymentioning
confidence: 90%
“…It has been suggested that the thymic stroma is the initial target of androgen-induced thymic atrophy [57,67] ; however, these studies failed to account for the role of bone marrow and thymic lymphoid progenitors, which are also significantly increased following castration [13,16,17] . In the bone marrow, there is improved function in most steps of haematopoiesis from the earliest long-term haematopoietic stem cell (HSC) through to thymic progenitors [pers.…”
Section: Castration and Ovariectomymentioning
confidence: 90%
“…This highly dynamical system makes it very sensible and reactive to antigen stimulations, but also to immunosuppressive treatments. Moreover immunostimulatory and rejuvenation treatments are explored to stimulate the immune system in aging or after immunosuppression (Dudakov, Goldberg et al 2009;Lynch, Goldberg et al 2009). Several factors like Keratinocyte growth factor, Growth hormone, cytokines like IL-7, IL-15 or IL2, steroid hormones are implicated in aging process.…”
mentioning
confidence: 99%
“…Adoptive transfer of in vitro generated precursor T cells aids in thymic regeneration and even has long-lasting impacts on the thymus well after the transient progenitors have passed through the thymus; however, the mechanism behind this prolonged regeneration is poorly understood [100]. Among these therapies, sex steroid ablation has beneficial impacts on both the BM and thymus, reversing age-related thymic involution [56] and enhancing BM recovery following chemotherapy [98,101] and bone marrow transplantation [97]. These novel approaches to restore immune capacity through the translation of pre-clinical research are likely to result in the development of strategies to improve the outcome for a variety of patients who incur considerable morbidity and mortality from infections and relapse after high-dose chemotherapy and HSC transplant or following chemotherapy.…”
Section: Box 1 Strategies For Immune Regenerationmentioning
confidence: 96%
“…These include: administration of exogenous growth factors and cytokines, such as KGF, growth hormone, ghrelin, IL-7, IL-15, insulin-like growth factor-1, IL-12, or Flt3L; adoptive transfer of T cell precursors generated in vitro; the chemical or surgical ablation of sex steroids ( Figure 3) [45,56,61,97,98] While most of these treatments primarily promote thymopoiesis directly, KGF and sex steroid ablation enhance thymic regeneration by acting on thymic stromal cells [40,45,61,99]. However, the success of growth factors such as IL-7, growth hormone and Flt3L is equivocal [40,44].…”
Section: Box 1 Strategies For Immune Regenerationmentioning
confidence: 99%